Implementasi ERP Odoo Modul Point of Sale untuk Meningkatkan Operasional Ritel di Toko Ezie - Irmayanti, Ade; Wulandari, Niken; Soraya, Ayu (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2024)
Toko Ezie, a retail business in Nanga Bulik, Lamandau Regency, Central Kalimantan, specializes in selling furniture, household appliances, and bedroom accessories. Established in 2010, Toko Ezie still manages its operations manually, particularly in sales recording, inventory management, and financial tracking. This manual system causes problems such as data inconsistency, recording errors, and operational inefficiencies. This research aims to analyze the requirements and benefits of implementing an Enterprise Resource Planning (ERP) system, specifically the Point of Sale (POS) module, to improve Toko Ezie’s operational efficiency and effectiveness. This study uses a qualitative descriptive approach with a case study method. Data were collected through interviews, observations, and documentation from the owner and staff of Toko Ezie. The research findings indicate that the implementation of an Odoo-based ERP system in the POS module will automate sales processes, monitor stock in real-time, and streamline financial recording. The integration between the POS, inventory, and financial modules is expected to minimize manual errors, improve data accuracy, and optimize customer service. This ERP implementation is anticipated to provide a long-term solution for enhancing the business performance of Toko Ezie.